Analyzing land suitability for key cereal crops in Mansa Watershed, Southwest Ethiopia - Wude Taye; Wakshum Shiferaw; Genaye Tsegaye (PLoS ONE, 2025)
This study is vital for helping farmers to produce appropriate crops based on physical land suitability and for assisting land use planners in decision-making. Large-scale crop production is essential to supply raw materials for industries, focusing on areas with high production potential to boost yields and meet growing demand. However, physical land suitability analysis for major cereal crops is lacking in Mansa Watershed of Southwest Ethiopia. Therefore, this research aimed to assess the physical land suitability for key crops such as wheat, maize, and teff. Utilizing the FAO land evaluation framework, the study employed various data sets, including Sentinel-2A satellite images, soil data, climate information, and elevation models, to determine suitability factors. The Analytical Hierarchy Process (AHP) was used for pairwise comparison of parameters, while Geographic Information System (GIS) software’s weighted overlay tool was applied to evaluate suitability for the specified crops. A vector overlay was utilized for land allocation for each crop. The analysis considered ten criteria: soil pH, depth, texture, drainage, organic matter, slope, altitude, rainfall, temperature, and land use change. Results indicated that approximately 29.6%, 61%, and 50% of the study area were moderately suitable for maize, teff, and wheat production, respectively. Additionally, 52.8%, 38.8%, and 13.9% of the area were marginally suitable for these crops, while 17.6% and 36% of the area were unsuitable for maize and wheat, respectively. Overall, 44% of the land was moderately suitable, and 10% was marginally suitable for the selected crops. Notably, there were no areas classified as highly suitable; most lands were identified as moderately or marginally suitable. Moving forward, sustainable land management practices are necessary to enhance land suitability and improve soil health. Further analyses should also consider irrigation facilities, market access, and processing industries to provide more options for stakeholders and policymakers.